Congenital chloride-losing diarrhea in a Mexican child with the novel homozygous SLC26A3 mutation G393W - Reimold, Fabian R.; Balasubramanian, Savithri; Doroquez, David; Shmukler, Boris E.; Zsengeller, Zsuzsanna K.; Saslowsky, David; Thiagarajah, Jay; Stillman, Isaac E.; Lencer, Wayne; Wu, Bai-Lin; Villalpando-Carrion, Salvador; Alper, Seth L. (Frontiers in Physiology, 2015)
Congenital chloride diarrhea is an autosomal recessive disease caused by mutations in the intestinal lumenal membrane Cl-/HCO3- exchanger, SLC26A3. We report here the novel SLC26A3 mutation G393W in a Mexican child, the first such report in a patient from Central America. SLC26A3 G393W expression in Xenopus oocytes exhibits a mild hypomorphic phenotype, with normal surface expression and moderately reduced anion transport function. However, expression of HA-SLC26A3 in HEK-293 cells reveals intracellular retention and greatly decreased steady-state levels of the mutant polypeptide, in contrast to peripheral membrane expression of the wildtype protein. Whereas wildtype HA-SLC26A3 is apically localized in polarized monolayers of filter-grown MDCK cells and Caco2 cells, mutant HA-SLC26A3 G393W exhibits decreased total polypeptide abundance, with reduced or absent surface expression and sparse punctate (or absent) intracellular distribution. The WT protein is similarly localized in LLCPK1 cells, but the mutant fails to accumulate to detectable levels. We conclude that the chloride-losing diarrhea phenotype associated with homozygous expression of SLC26A3 G393W likely reflects lack of apical surface expression in enterocytes, secondary to combined abnormalities in polypeptide trafficking and stability. Future progress in development of general or target-specific folding chaperonins and correctors may hold promise for pharmacological rescue of this and similar genetic defects in membrane protein targeting.